Application of the 2019 ESC/EAS dyslipidaemia guidelines to nationwide data of patients with a recent myocardial infarction: a simulation study. (18th February 2020) - Allahyari, Ali; Jernberg, Tomas; Hagström, Emil; Leosdottir, Margrét; Lundman, Pia; Ueda, Peter
Abstract: Aims: To estimate the proportion of patients with a recent myocardial infarction (MI) who would be eligible for additional lipid-lowering therapy according to the 2019 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guidelines for the management of dyslipidaemias, and to simulate the effects of expanded lipid-lowering therapy on attainment of the low-density lipoprotein cholesterol (LDL-C) target as recommended by the guidelines. Methods and results: Using the nationwide SWEDEHEART register, we included 25 466 patients who had attended a follow-up visit 6–10 weeks after an MI event, 2013–17. While most patients (86.6%) were receiving high-intensity statins, 82.9% of the patients would be eligible for expanded lipid-lowering therapy, as they had not attained the target of an LDL-C level of <1.4 mmol and a ≥50% LDL-C level reduction. When maximized use of high-intensity statins followed by add-on therapy with ezetimibe was simulated using a Monte Carlo model, the LDL-C target was reached in 19.9% using high-intensity statin monotherapy and in another 28.5% with high-intensity statins and ezetimibe, while 50.7% would still be eligible for proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. When use of alirocumab or evolocumab was simulated in those who were eligible for PCSK9 inhibitors, around 90% of all patients attained the LDL-C target. Conclusion : Our study suggests that, even with maximized use of high-intensity statins and ezetimibe, around half of patients with MI would be eligible for treatment with PCSK9 inhibitors according to the 2019 ESC/EAS guidelines. Considering the current cost of PCSK9 inhibitors, the financial implications of the new guidelines may be substantial.